Military Expenditure and Arms Trade : Alternative Data Sources - Wakeman-Linn, John (IMF Working Papers; Working Paper ;, 1994)
Analysis of the economic impact of military expenditures and arms trade is frequently hampered by the limited amount of transparent, comprehensive data. Country-specific information can be supplemented, however, by data from multicountry statistical sources. This paper describes seven publications which provide multicountry statistics on military expenditure and trade--the information each source conveys, as well as the differences in coverage and definition--to assist the analyst in understanding how to use this data. Comparisons of the data reported by the various sources reveal numerous, significant differences, particularly in data on military expenditures.